Observations of fish fauna in the upper reaches of the rivers Ekareuyakha and Mongocheyakha (Gydan peninsula) - Volokh, Anatolii; Волох, Анатолий Михайлович; Волох, Анатолій Михайлович (My University, 1998)
EN: The material was collected in summer in the course of the International Arctic Expedition of the Institute of Evolutionary Morphology and Ecology of Animals, RAS. RU: Материал собран летом 1989 г. ю время работы Международной Арктической экспедиции ИЭМЭЖ РАН. Отлов рыб проводился лесковой сетью длиной 8 м (размер ячеи 30 мм).
Наблюдения за ихтиофауной верховий рек Екареуяхи и Монгочеяхи (Гыданский полуостров
Keywords: отлов рыб; ихтиофауна; fish